2013
DOI: 10.1128/jcm.00759-13
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Human Genomic and Human Papillomavirus DNA Stored in BD SurePath and Hologic PreservCyt Liquid-Based Cytology Media

Abstract: We evaluated the effect of storage at 2 to 8°C on the stability of human genomic and human papillomavirus (HPV) DNA stored in BD SurePath and Hologic PreservCyt liquid-based cytology media. DNA retained the ability to be extracted and PCR amplified for more than 2.5 years in both medium types. Prior inability to detect DNA in archived specimens may have been due to failure of the extraction method to isolate DNA from fixed cells. Liquid-based cytology (LBC) media (BD SurePath [Becton, Dickinson and Company] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…A 0.5 ml aliquot of thoroughly vortexed SurePath or PreservCyt was added to 1.7 ml of a proprietary HPV diluent. A heat step was employed to ensure that exfoliated cells were lysed and the sample homogenized prior to extraction of sample DNA [4], [5].The Genera PapType Test is a semi-automated, bead-based multiplex full genotyping DNA assay for 14 high-risk HPV types (16,18,31,33,35,39,45,51,52,56,58,59,66,68) and two low-risk HPV types (6,11). The Sirocco platform (Genera Biosystems, Scoresby, Australia) was used.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…A 0.5 ml aliquot of thoroughly vortexed SurePath or PreservCyt was added to 1.7 ml of a proprietary HPV diluent. A heat step was employed to ensure that exfoliated cells were lysed and the sample homogenized prior to extraction of sample DNA [4], [5].The Genera PapType Test is a semi-automated, bead-based multiplex full genotyping DNA assay for 14 high-risk HPV types (16,18,31,33,35,39,45,51,52,56,58,59,66,68) and two low-risk HPV types (6,11). The Sirocco platform (Genera Biosystems, Scoresby, Australia) was used.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Other retrospective and prospective published studies of hrHPV HC2 testing on SurePath TM specimens with abnormal cytology have reported sensitivities ranging from 93% to 100% for CIN 2 and higher. 27, 28 Castle et al found hrHPV HC2 on ThinPrepV R specimens was unaffected by a storage time of up to 8 years at ambient conditions, though cytomorphology and DNA recovery by PCR decreased significantly. 12,[14][15][16][17][18][19][20][21] The lowest sensitivity, reported by Evans et al, 17 was not replicated in other studies; in this study, the sensitivity was 50% for LSIL, but they had only 10 cases.…”
Section: Discussionmentioning
confidence: 99%
“…Siddiqi (2009) (retrospectively) and Zhao (2011) (cross sectionally) studied hrHPV HC2 testing on both Sure-Path TM and ThinPrepV R specimens and found the falsenegative rates to be comparable. 28,30 Low false-negative rates have been reported by Ko et al, who undertook a prospective validation study using routine clinical cases handled with specific specimen storage and processing protocols that take SurePath TM limitations into consideration (6.6% for CIN 2 and 5% for CIN 3, among cases with ASCUS cytology), 11 and by Qureshi et al compared to ThinPrepV R (4% vs. 6%, P 5 0.72) using PCR as gold standard. 27, 28 Castle et al found hrHPV HC2 on ThinPrepV R specimens was unaffected by a storage time of up to 8 years at ambient conditions, though cytomorphology and DNA recovery by PCR decreased significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the efficiencies of different methods for nucleic acid extraction from LBC specimens were examined. However, it was unclear how many cells were needed for detection in genetic analyses . We determined the number of cells necessary for the detection of DNA and RNA by PCR using bladder and cervical cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%